Ideal Model in the Implementation of National Insight Policies for Handling Social Conflict in Pandeglang Regency - Rusdjiman Soemaatmadja; Tjahya Supriatna; Hyronimus Rowa; Kusworo (International Journal of Science and Society, 2020)
Pandeglang Regency is one of the regencies located in Banten Province which is a strategic area because it is close to the capital city of the Republic of Indonesia. Its proximity to the capital causes Pandegalang Regency to have the potential for high social conflict. This is supported by data showing that the number of conflicts in Pandeglang Regency was the highest in Banten Province in 2011 although there was a tendency to decrease in the following year. To suppress the occurrence of social conflicts in Pandeglang District, the local government has implemented a National Insight Policy with a collaborative governance perspective. The research describes the factors that influence the implementation of these policies and tries to formulate an ideal method that can be used in the application of a national insight policy. This study uses a qualitative approach so that in interpreting the conditions of the actors, it is further developed by means of triangulation analysis. The results of the study found that there were several factors that influenced the implementation of the national insight policy such as the insufficient capability of the national insight education center team, low community participation, limited budget. In this study, researchers also tried to design a model for implementing the national insight policy in social conflict management.